Aquatic flora and fauna associated with the freshwater snail Lymnaea acuminata in Kham river at Aurangabad (M.S.) - Nagare, K R; Dummalod, C B (International Multidisciplinary Research Journal, 2012)
The present study includes considerable variations in aquatic flora and fauna recorded in Kham River during the period of Jun. 2009 – Sept. 2009. Lymnaea work as vector for various trematode pathogens and it is common in the bitant of the Kham River.Hence the present investigation was undertaken to study other associate flora and fauna in the vicinity of the snail Lymnaea acuminata with their relationship. Density of the molluscan species carried out with the study.